2023
DOI: 10.5194/egusphere-2023-1290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gas-particle partitioning of toluene oxidation products: an experimental and modeling study

Abstract: Abstract. Aromatic hydrocarbons represent a large fraction of anthropogenic volatile organic compounds and significantly contribute to tropospheric ozone and secondary organic aerosol (SOA) formation. Toluene photooxidation experiments were carried out in an oxidation flow reactor (OFR). We identified and quantified the gaseous and particulate reaction products at 280, 285 and 295 K using a proton-transfer reaction time-of-flight mass spectrometer (PTR-ToF-MS) coupled to a CHemical Analysis of aeRosol ONline (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…We then grouped these products into extremely low volatility (saturation concentration (C*) ≤ 3 × 10 −4 μg m −3 ), low volatility (3 × 10 −4 < C* ≤ 0.3 μg m −3 ), semivolatile (0.3 < C* ≤ 300 μg m −3 ), intermediate volatility (300 < C* ≤ 3 × 10 6 μg m −3 ), and volatile (C* > 3 × 10 6 μg m −3 ) categories as shown in Figure S6 of Supporting Information . Based on the volatility distribution of toluene SOA, we found that semivolatile organic compounds (SVOCs) contributed about 49.6% of total SOA mass concentration (TS2‐3), which is slightly lower than observed fractions (62%–71%) for toluene SOA produced in an oxidation flow reactor (OFR) with a comparable initial toluene condition but lower temperature (Lannuque et al., 2023). This difference might be attributed to differences in initial toluene concentrations, experimental temperature, and speciation variation among toluene oxidation products generated under different reaction durations between OFR and chambers.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We then grouped these products into extremely low volatility (saturation concentration (C*) ≤ 3 × 10 −4 μg m −3 ), low volatility (3 × 10 −4 < C* ≤ 0.3 μg m −3 ), semivolatile (0.3 < C* ≤ 300 μg m −3 ), intermediate volatility (300 < C* ≤ 3 × 10 6 μg m −3 ), and volatile (C* > 3 × 10 6 μg m −3 ) categories as shown in Figure S6 of Supporting Information . Based on the volatility distribution of toluene SOA, we found that semivolatile organic compounds (SVOCs) contributed about 49.6% of total SOA mass concentration (TS2‐3), which is slightly lower than observed fractions (62%–71%) for toluene SOA produced in an oxidation flow reactor (OFR) with a comparable initial toluene condition but lower temperature (Lannuque et al., 2023). This difference might be attributed to differences in initial toluene concentrations, experimental temperature, and speciation variation among toluene oxidation products generated under different reaction durations between OFR and chambers.…”
Section: Resultsmentioning
confidence: 92%
“…Lannuque et al. (2023) found that MCM overestimated gaseous products with high carbon numbers (C 7 ) and their oxidation state compared to gas‐ and particle‐phase products detected in toluene SOA experiments. Consequently, the contribution of C 7 products to toluene SOA was overpredicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last decade, online high-resolution instrumentation has been developed for the identification of the OA species at a molecular level (Williams et al, 2006(Williams et al, , 2014Kreisberg et al, 2009;Hohaus et al, 2010;Zhang et al, 2014) or for the identification of the chemical formula using soft-ionization mass spectrometry (Lopez-Hilfiker et al, 2014;Isaacman-VanWertz et al, 2017;Stark et al, 2017;Gkatzelis et al, 2018;Lannuque et al, 2023). Volatility measurements are performed by alternative measurements between the gas and the particle phase of the same ion (Hohaus et al, 2015;Lopez-Hilfiker et al, 2016;Isaacman-VanWertz et al, 2016;Stark et al, 2017;Gkatzelis et al, 2018;Lannuque et al, 2023). To our knowledge these new techniques are still limited.…”
mentioning
confidence: 99%
“…To our knowledge these new techniques are still limited. They have been applied to biogenic OA systems in the ambient (Lopez-Hilfiker et al, 2016;Isaacman-VanWertz et al, 2016;Stark et al, 2017) or in laboratory produced biogenic SOA (Hohaus et al, 2015;Gkatzelis et al, 2018), and just recently on toluene SOA (Lannuque et al, 2023).…”
mentioning
confidence: 99%